2008
DOI: 10.1007/s00330-008-1055-1
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-guided removal of Implanon™ devices

Abstract: Our study has shown that ultrasound-guided localisation and removal of Implanon rods is safe, practical and highly successful. Over a 4-year period, 119 patients had successful, uncomplicated removal of their subdermal devices.The technique is particularly useful for removal of the device when it is not palpable or when an attempt at removal of a palpable device has not been successful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…The more likely explanation for impalpable implants is incorrect placement into deeper tissues or non-insertion 2 5 13. The side effects experienced by our patient seem to indicate incorrect insertion of the subcutaneous implant.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…The more likely explanation for impalpable implants is incorrect placement into deeper tissues or non-insertion 2 5 13. The side effects experienced by our patient seem to indicate incorrect insertion of the subcutaneous implant.…”
Section: Discussionmentioning
confidence: 68%
“…The removal process is also straightforward, providing insertion has been done correctly, with an average time of 3.6 min 7. The low doses of progestogens delivered clear rapidly from the system after implant removal, with the consequent resumption of ovarian function within approximately 3 weeks 2 6 8 9…”
Section: Discussionmentioning
confidence: 99%
“…The recommended location of the insertion site is such that, while cosmetically hidden, the deeply placed implant puts the ulnar neurovascular bundle at significant risk. Studies have identified nonpalpable implants using intraoperative image intensifiers (X-rays) when a radioopaque implant is used [1], US preoperatively [2], US intraoperatively [5] and preoperative magnetic resonance imaging [6]. Invasive US-guided localization is also described, whereby a hook wire marker is placed near to the implant under US guidance [7].…”
Section: Discussionmentioning
confidence: 98%
“…Non-palpable subdermal implants can result from suboptimal placement, the development of a dense fibrous sheath, or an increase in subcutaneous fat since the time of placement [3]. We present cases in which the gynecologist uses ultrasound guidance to both locate and remove non-palpable subdermal contraceptive devices.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the reports on implant removals are by radiologists [2,3,6]. Removal by the gynecologist, on the other hand, may result in increased patient comfort as she is in the presence of her familiar gynecologist.…”
Section: Discussionmentioning
confidence: 99%